The ordination of women: Biblical perspectives - Duff, Nancy J. (Theology today, 2016)
This essay focuses on one aspect of the debate regarding the ordination of women by analyzing and challenging interpretations and translations of specific biblical passages that have often been used to argue against the ordination of women. It provides reflections on only one aspect of a much broader discussion that even members of denominations that have long ordained women should not ignore.